Evaluation of Data Extracted from Floor Plans for Apartment Complex Remodeling - Shin, Dongik; Ryu, Hyeongmin; Kim, Jeeyeop; Kim, Jinyoung (Advances in Civil Engineering, 2022)
South Korea has witnessed an increasing social demand for housing supply due to rapid urban population growth from the 1950s through the 1970s. At least two million houses have been in use for 30 years or more since the implementation of policies related to the mass production of apartment houses 20-30 years ago. Methods for improving the aging of domestic apartment houses and their living environment are reconstruction and remodeling, and the government has been encouraging remodeling by easing laws and regulations related to it. During the early stages of a typical remodeling project, many candidate floor plans arise in the process of finalizing the floor plan, resulting in significant time consumption in the iterative process for reviews and revisions. Extracting quantitative indicators by comparing floor plans before and after remodeling at the initial design stage and comparing the indicators of the target complex with the existing case can facilitate a more time-efficient and economical decision-making process. In this study, quantitative indicators were extracted from floor plans by applying a structural evaluation program for remodeling of apartment housing at five existing domestic apartment complexes (nine buildings in total), and a detailed comparative analysis was conducted. Evaluated indices included variations of floor area, load-bearing wall, nonbearing wall, slab, weight, area moment of inertia, torsional resistance, and visualization of removed, remaining, and new bearing walls. The proposed method can continuously accumulate data from domestic apartment house remodeling projects and accelerate the process by shortening the time required for final decision-making in future remodeling projects.